Pemanfaatan Nanobubble Karbon Dioksida untuk Memperpanjang Umur Simpan Tomat: Analisis Susut Bobot dan Kenampakan Visual - Rosalinda, S.; Khoiriyah, Nurul; Alam, Hilman Syaeful (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Tomatoes, as a horticultural commodity, face major postharvest challenges due to their high water content and continued respiration after harvest, which lead to rapid deterioration. This results in significant economic losses for both farmers and consumers. This study aims to analyze the effect of carbon dioxide (CO₂) nanobubble technology applied through a mist generator on weight loss and visual appearance of tomatoes during storage, as a preventive solution to postharvest damage. The research method involved producing nanobubble solution by injecting CO₂ gas into water using a nanobubble generator to form nanoscale bubbles. The resulting solution was applied in mist form directly onto the tomato surface using a mist generator prior to storage. Evaluation was conducted by quantitatively measuring weight loss and qualitatively assessing visual appearance over a 14-day storage period at room temperature. The results showed that CO₂ nanobubble treatment via mist generator reduced weight loss by up to 4% compared to the untreated control. This technology was also effective in maintaining the freshness and visual quality of tomatoes during extended storage. These findings confirm that carbon dioxide nanobubble application through a mist generator is a promising and environmentally friendly alternative technology for extending the shelf life of fresh horticultural produce.